The Gender Pay Gap Under Duopsony: Joan Robinson Meets Harold Hotelling - Hirsch, Boris (Scottish Journal of Political Economy, 2009)
This paper presents an alternative explanation of the gender pay gap resting on a simple Hotelling-style duopsony model of the labour market. Since there are only two employers, equally productive women and men have to commute and face travel cost to do so. We assume that some women have higher travel cost, e.g., due to more domestic responsibilities. Employers exploit that women on average are less inclined to commute and offer lower wages to all women. Since women's firmlevel labour supply is for this reason less wage-elastic, this model is in line with Robinson's explanation of wage discrimination. © 2009 The Author Journal compilation © 2009 Scottish Economic Society. Published by Blackwell Publishing Lt
WiSo-Import:2015-03-26:4098